2012
DOI: 10.1074/jbc.m112.417212
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Interaction Molecule 1 (STIM1) Is Involved in the Regulation of Mitochondrial Shape and Bioenergetics and Plays a Role in Oxidative Stress

Abstract: Background: Store-operated Ca 2ϩ entry is regulated by the sensor STIM1 and the channel ORAI1. Results: Deficiency alters mitochondrial shape and increases mitochondrial activity resulting in increased susceptibility to oxidative stress and cell death by nuclear translocation of apoptosis-inducing factor. Conclusion: Store-operated Ca 2ϩ entry regulates mitochondrial function and vulnerability. Significance: STIM1 plays a role in oxidative stress by regulating mitochondrial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 37 publications
(46 reference statements)
4
39
2
Order By: Relevance
“…Moreover, in STIM1 null cells they found that normal mitochondrial structure was disrupted and metabolic rate increased. It has also been shown that STIM1 is s-glutathionylated in response to oxidative stress, resulting in increased SOCE and altered mitochondrial Ca 2ϩ homeostasis (29); however, contrary to the work of Henke et al (30) they found that a reduction in STIM1/Orai1 is protective in terms of oxidative stress. These studies provide evidence that STIM1 contributes to the regulation of both mitochondrial homeostasis and oxidative stress.…”
Section: Potential Role For Stim1-mediated Soce In Ischemia/reperfusicontrasting
confidence: 53%
See 2 more Smart Citations
“…Moreover, in STIM1 null cells they found that normal mitochondrial structure was disrupted and metabolic rate increased. It has also been shown that STIM1 is s-glutathionylated in response to oxidative stress, resulting in increased SOCE and altered mitochondrial Ca 2ϩ homeostasis (29); however, contrary to the work of Henke et al (30) they found that a reduction in STIM1/Orai1 is protective in terms of oxidative stress. These studies provide evidence that STIM1 contributes to the regulation of both mitochondrial homeostasis and oxidative stress.…”
Section: Potential Role For Stim1-mediated Soce In Ischemia/reperfusicontrasting
confidence: 53%
“…In addition, the ER stress protein ERp57 has been shown to interact with STIM1 and modulate SOCE (94). Henke et al (30) also found that in STIM1-deficient cells there was increased phosphorylation of EReIF2␣ and PERK, further supporting a role for STIM1 in mediating ER stress response.…”
Section: Orai1/trpcmentioning
confidence: 80%
See 1 more Smart Citation
“…SOCE was quantified by a highthroughput method previously validated using STIM1 − / − mouse embryonic fibroblasts and shown to be reliable. 40 Ratiometric Fura2-AM values were converted to absolute Ca 2+ values as described 41 and analyzed with Attovision (BD Bioscience). For measuring the Ca 2+ kinetics of B and T cells, splenocytes were incubated with 3 μM Fluo8 for 30 min at RT.…”
Section: Ca 2+ Measurementsmentioning
confidence: 99%
“…STIM1 is a transmembrane ER protein containing multiple functional domains, and it serves as an ER Ca 2ϩ sensor and activator of store-operated Ca 2ϩ entry (SOCE) (44 -46). Studies have shown that Stim1 is associated with oxidative stress and mitochondrial bioenergetics (47). We found that suppression of Stim1 in Sertoli cells in the cultured testis in vitro increased ROS production and caused a global disruption of gonads, evidenced by disorganized testicular cord formation, obstruction of angiogenesis, and loss of interstitium.…”
Section: Discussionmentioning
confidence: 72%